THE PRODUCTIVITY OF WORKERS OF LOCOMOTIVE FACILITIES OF UKRZALIZNYTSIA - Romanko, V. I.; Romanko, O. V. (Science and Transport Progress, 2009)
An analysis of the factors, which influence on the change of labour productivity of the Ukrainian locomotive workers, is presented.